Membranous NECTIN-4 Expression Frequently Decreases during Metastatic Spread of Urothelial Carcinoma and Is Associated with Enfortumab Vedotin Resistance - Klümper, Niklas; Ralser, Damian J.; Ellinger, Jörg; Roghmann, Florian; Albrecht, Julia; Below, Eduard; Alajati, Abdullah; Sikic, Danijel; Breyer, Johannes; Bolenz, Christian; Zengerling, Friedemann; Erben, Philipp; et al. (Clinical Cancer Research, 2023)
Purpose: The antibody–drug conjugate enfortumab vedotin (EV) releases a cytotoxic agent into tumor cells via binding to the membrane receptor NECTIN-4. EV was recently approved for patients with metastatic urothelial carcinoma (mUC) without prior assessment of the tumor receptor status as ubiquitous NECTIN-4 expression is assumed. Our objective was to determine the prevalence of membranous NECTIN-4 protein expression in primary tumors (PRIM) and patient-matched distant metastases (MET). Experimental Design: Membranous NECTIN-4 protein expression was measured (H-score) by IHC in PRIM and corresponding MET (N ¼ 137) and in a multicenter EV-treated cohort (N ¼ 47). Progression-free survival (PFS) after initiation of EV treatment was assessed for the NECTIN-4–negative/weak (H-score 0–99) versus moderate/strong (H-score 100–300) subgroup. The specificity of the NECTIN-4 IHC staining protocol was validated by establishing CRISPR-Cas9–induced polyclonal NECTIN-4 knockouts. Results: In our cohort, membranous NECTIN-4 expression significantly decreased during metastatic spread (Wilcoxon matched pairs P < 0.001; median H-score ¼ 40; interquartile range, 0–140), with 39.4% of MET lacking membranous NECTIN-4 expression. In our multicenter EV cohort, absence or weak membranous NECTIN-4 expression (34.0% of the cohort) was associated with a significantly shortened PFS on EV (log-rank P < 0.001). Conclusions: Membranous NECTIN-4 expression is frequently decreased or absent in mUC tissue. Of note, the clinical benefit of EV strongly depends on membranous NECTIN-4 expression. Thus, our results are of highest clinical relevance and argue for a critical reconsideration of the current practice and suggest that the NECTIN-4 receptor status should be determined (ideally in a metastatic/progressive lesion) before initiation of EV.
CRIS-Team Scopus Importer:2023-05-26